PENGARUH PROMOSI SEKOLAH DAN PELAYANAN PENDIDIKAN MELALUI PERILAKU WALI MURID TERHADAP KEPUTUSAN MEMILIH SEKOLAH MENENGAH PERTAMA ISLAM TERPADU ABDURRAB DI KOTA PEKANBARU - Irfan Teguh; Rahayu Danar Deny; Wasnury Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
A decision is a selection of two or more alternative choices. In other words, aconsumer must have a choice between making a purchase or not making apurchase. This study aims to see the effect of school promotion and educationservices through the behavior of student guardians on the decision to choose theAbdurrab Integrated Islamic Junior High School in Pekanbaru City. Thisresearch was conducted using primary data collected from respondents throughquestionnaires, while the respondents consisted of 152 parents of students atAbdurrab Integrated Islamic Middle School Pekanbaru City who met the criteria.Then a hypothesis test was carried out using path analysis with the help of SPSSVersion 25.0. In this study shows that; 1) there is a significant effect of SchoolPromotion on Guardian Student Behavior, 2) there is a significant effect onEducation Services on Guardian Student Behavior, 3) there is a significant effecton School Promotion on Choosing Decision, 4) there is a significant effect ofEducation Services on Choosing Decision, 5) there is a significant effect ofGuardian Student Behavior on Choosing Decision, 6) there is a significant effectof School Promotion on Choosing Decision through Student Guardian Behavior,7) there is a significant effect of Education Services on Choosing Decisionthrough Student Guardian Behavior Keywords : School Promotion, Educational Services, Guardian Behavior,Choosing Decision.